The Perception of Islamism by the Teachers and Students of Pesantren Mawaridussalam Deli Serdang, North Sumatra - Dahlia Lubis (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2019)
Many studies on pesantren in Indonesia emphasize more on the aspect of this establishment as the oldest Islamic educational institution in the archipelago only, instead of other aspects related to this type of school. Recently, a growing number of studies have shifted their topic into one particular focus, which is radicalism or Islamism in pesantren. Consequently, this paper aims to examine the responses of pesantren teachers and students to the term ‘Islamism’. The study was conducted at Pesantren Mawaridussalam, an Islamic boarding school located in Batang Kuis village, Deli Serdang, which is in North Sumatra, Indonesia. Specifically, the responses of teachers and students to the issue of the Islamic state were elaborated. The study also focused on shariazation, which seeks to make Islam the state law, as well as democracy, and jihād, which is a struggle or fight against the enemies of Islam the religion. The findings of this study indicate that the teachers and students had varied understandings of Islamism as some argued that the term was close to Islamists, while others believed that it was identical. Despite the different understandings, most of them rejected the use of violence in fighting for the ideals of Islam.